Transformasi Pendidikan Sekolah Dasar Menuju Sekolah Ramah Anak Melalui Program Mahasiswa KKN MBKM FH UNRI Desa Sungai Jalau - Erdiansyah, Erdiansyah; Marchinda, Cecilia Karen; Pasaribu, Cindy Deborah Novlisya; Maulana, Dirga; Febri, Handra Asrio; Ariqoh, Hafidh Yean; Haikal, Haikal; Siregar, Riska Septiani; Fitri, Wan Mardhiyyaul; Wulandari, Yuli Arisa; Aulia, Zakkiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Bullying in elementary schools remains a serious issue that affects students’ psychological well-being and academic performance. The 2025 KKN MBKM Program of Universitas Riau at SDN 011 Sungai Jalau was implemented as a preventive effort to create a safe, comfortable, and child-friendly school environment. The activities included observation, questionnaire distribution, data analysis, socialization for teachers, and the provision of a complaint box as a safe reporting medium for students. Based on the survey results, 83.9% of students stated that they had experienced or witnessed bullying, while 16.1% stated that they had not, indicating that bullying practices are still quite high in the school environment. After the socialization and introduction of the complaint box, the school community showed increased awareness and proactive responses in handling student reports. Overall, this program not only improved understanding of bullying prevention but also fostered a caring culture, mutual respect, and early prevention to support the realization of a child-friendly school.